(untitled) (Editora Impacto Científico, 2025)
Diabetes is a group of metabolic diseases characterized by hyperglycemia and associated with complications, dysfunction and failure of various organs, especially the eyes, kidneys, nerves, brain, heart and blood vessels. The aging of the population, increasing urbanization and the adoption of unhealthy lifestyles such as sedentary lifestyles, poor diet and obesity are largely responsible for the increase in the incidence and prevalence of diabetes worldwide. (BRASIL,2016) Diabetic neuropathy stands out as one of the most prevalent and debilitating complications of diabetes. This condition results from damage to the peripheral nerves caused by prolonged hyperglycemia, manifested by symptoms ranging from pain and tingling to loss of sensation in the extremities. According to Cruz and Lima (2015), it is estimated that around 50% of individuals with type 1 and type 2 diabetes develop some form of neuropathy throughout their lives. Given this scenario, the aim of this study was to inform people about the possible complications that untreated diabetes can cause, especially diabetic neuropathy. Stressing the importance of daily care and treatment for a better quality of life. In order to achieve these objectives, a website was created containing information in accessible and simple language on diabetes management, which was disseminated in the community and on the authors’ social networks.